Body mass index as a predictor of severity in burn injury: a retrospective analytical study - Durazo, Adda María Sánchez; Torón, Juan Carlos Hernández; Palomares, Kenia Selene Avilés; Caprielova, Yuri Jiménez; Riojas, Patricia Sofía Elguezabal; Covarrubias, Carlos Francisco Morales (International Surgery Journal, 2025)
Background: Obesity has been identified as an independent risk factor influencing outcomes in trauma and critical illness. In burn patients, excess weight may exacerbate metabolic demand, impair wound healing, and increase mortality. Objective of the study was to determine whether body mass index (BMI) serves as a predictor of severity in hospitalized burn patients and to assess whether incorporating BMI into the abbreviated burn severity index (ABSI) improves its prognostic accuracy. Methods: A retrospective, analytical, and cross-sectional study was conducted at the Burn and Intensive Care Units of the “Dr. Victorio de la Fuente Narváez” Hospital, Instituto Mexicano del Seguro Social (IMSS), from January 2016 to January 2020. Clinical records were reviewed to obtain demographic, anthropometric, and clinical data. Sensitivity and specificity analyses were performed to determine the optimal BMI cutoff for mortality prediction. Results: Seventy adult burn patients met inclusion criteria. The mean BMI among survivors was 26.7±3.9 kg/m² and among non-survivors 30.5±4.9 kg/m² (p=0.03). A BMI cutoff of 28 kg/m² yielded an AUC of 0.748 (95% CI 0.68-0.88; p=0.003), with 0.80 sensitivity and 0.69 specificity for mortality prediction. Mortality was significantly higher among patients with BMI ≥28 kg/m² (80%) compared to those below this threshold (32.7%; p=0.0003). The standard ABSI system maintained high predictive accuracy (sensitivity=86.6%, specificity=100%). Conclusions: BMI ≥28 kg/m² adversely affects survival in adult burn patients. Although the ABSI remains a highly accurate tool, incorporating BMI could enhance its prognostic power.